The Effect of the Application of Composts with different Compositions on Soil Fertility and Cotton Yield - Alisher, Sayimbetov (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the effect of the use of composts of different compositions, prepared by mixing phosphogypsum in different proportions on cattle manure, poultry manure, rice and wood chips, on the agrophysical properties and fertility of the soil and cotton yield. At the same time, the volume mass of the soil decreased to 0.04-0.07 g / cm3, porosity increased to 2.2-2.7%, humus increased by 0.115%, total nitrogen by 0.010% and total phosphorus by 0.014%. As a result, in the variant where compost-2 (in the ratio 1: 1: 1.4: 0.6) was applied at 20 t / ha, it was noted that cotton grew rapidly and yielded an additional yield of 6.7 t / ha of cotton.